Correlation among students learning styles, learning motivation and the eleventh grade students’ speaking ability - Sunaidah Sunaidah; Baginda Simaibang; Mulyadi Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine the correlation among students’ learning styles, learning motivation, and the eleventh grade students’ speaking ability at MAN 1 Musi Banyuasin Sekayu. The research was conducted correlation research design. This study’s population comprised eleventh grade students of MAN 1 Musi Banyusin Sekayu, sampling through a purposive sampling of 30 students. Data collection techniques used include questionnaire and test. Based on the study results the data showed that (1) there is not any significant correlation between learning styles and speaking ability with a correlation value of 0,590; (2) there is not any significant correlation between learning motivation and speaking ability with a correlation value of 0.706; (3) there is not any significant correlation between learning styles and learning motivation with a correlation value of 0,233; (4) there is not any significant correlation among learning styles, learning motivation and speaking ability with correlation value 0,838.